The Enforcement of Anti-Money Laundering Laws in Cryptocurrency Transactions: A Comparative Legal Analysis - Dr Rizwana Gul; Adnan Nisar; Dr. Mohammad Jan (Social Science Review Archives, 2025)
The emergence of cryptocurrency has posed a serious problem to the implementation of the Anti-Money Laundering (AML) laws because the digital currencies are decentralized and anonymous. The paper will analyze the application of the AML regulations in cryptocurrency transactions by providing a comparative legal study of three major jurisdictions, that is the United States, European Union, and different countries in Asia. The paper discusses the jurisdictions such as the U.S. and the EU which have adopted cryptocurrency service providers into their current AML systems whereas other countries in the Asian region, including Japan, China, and Singapore, have come up with opposite policies on cryptocurrency regulation. The discussion examines the legal and technological implications of implementing the classic AML actions in relation to cryptocurrency like the question of anonymity, jurisdictional constraints, and the fast-paced development of financial technologies. The results indicate that whereas certain jurisdictions have made it, international collaboration and harmonized regulatory frameworks are essential in the effort to effectively counter money laundering in cryptocurrencies transactions. The policy recommendations on how to implement AML enforcement better are identified as the standardization of the rules, the increased international collaboration, and the changes in the current legal frameworks to respond to the new threat of decentralized finance (DeFi) and privacy coins at the conclusion of the paper.